Numerical simulation of closest vane thermal performance in large aperture Space Solar Telescope. (25th June 2016) - Li, Rong; Wang, Sen; Wu, Mingchang; Chen, Zhiping; Zhang, Juyong
Highlights: A thermal-scattering integrated design of vanes in solar telescopes is proposed. The closest vane increases the maximal temperature of the primary mirror. Three series of closest vane models are constructed with the same thermal design. Effects of geometric parameters of closest vane on the primary mirror temperature are investigated. Vertical closest vane with S 1 < 960 mm and D < 20 mm is figured out and optimized. Abstract: Since large aperture & small field of view (FOV) solar telescopes operate in special environment, thermal design is a key to achieve excellent optical performance. A thermal-scattering integrated design on vanes in large aperture & small FOV solar telescopes is proposed to obtain high signal to noise ratio and high spatial resolution. The present study is aimed to investigate the importance of additional thermal effect on the primary mirror caused by closest vane with various geometrical parameters. Three series of thermal models of Space Solar Telescope (SST) are developed to investigate the effects on the primary mirror temperature for its original thermal design after adding closest vane. Thermal variation based on three different geometrical parameters for these models are analyzed and the importance of the additional thermal effects of closest vane are identified and discussed. Suggestion is proposed to optimize three geometrical parameters of closest vane in thermal-scattering integrated design of SST.